A multilayer composite solid electrolyte and its preparation method and application

By adopting the preparation method of multi-layer composite solid electrolyte in lithium-ion batteries, the problems of poor fluidity and poor interface contact in lithium-ion batteries are solved, and the cycle stability and voltage window of the battery are improved.

CN119419354BActive Publication Date: 2025-05-02ZHUJI PAWA NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510020211.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-05-02
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

After using solid electrolytes, existing lithium-ion batteries have poor fluidity and poor interface contact, which affects the cycling stability and energy density of the battery.

Method used

By adopting the preparation method of a multi-layer composite solid electrolyte, slurries of different compositions are coated on the negative electrode side, the intermediate layer and the positive electrode side, and a multi-layer structure is formed after drying, including lithium salt A, polymer and solvent slurries A, lithium salt B, polymer, MOF and solvent slurries B, lithium salt C, polymer and solvent slurries C.

Benefits of technology

Through the multi-layer composite design, the cycle stability and voltage window of the battery are improved, the stability of lithium-ion batteries to high voltage and the adaptability of lithium are enhanced, and the problems of poor fluidity of solid electrolytes and poor interface contact are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419354B_ABST
    Figure CN119419354B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and discloses a multi-layer composite solid electrolyte, a preparation method thereof, and an application. The preparation method includes mixing lithium salt A, a polymer, and a solvent to obtain slurry A, and drying slurry A to prepare a negative electrode side solid electrolyte; mixing lithium salt B, a polymer, MOF, and a solvent to obtain slurry B, coating slurry B on the negative electrode side solid electrolyte membrane, and drying to obtain an intermediate product; mixing lithium salt C, a polymer, and a solvent to obtain slurry C, coating slurry C on the intermediate product, and drying to obtain the multi-layer composite solid electrolyte; lithium salt A is prepared by mixing any one of LiBOB and LiDFOB with LIFSI; lithium salt C is prepared by mixing any one of LiDFP and LiNO3 with LIFSI. The prepared multi-layer composite solid electrolyte can improve the cycle stability and voltage window of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a solid electrolyte, in particular to a multilayer composite solid electrolyte and a preparation method thereof. Background Art

[0002] The research on electrical energy storage materials and devices has always been a hot topic in the scientific research community. Chemical power sources are the most efficient and long-life energy storage devices. Among them, lithium-ion batteries have been favored by people for their high energy density and high rate performance since their commercial application in 1990. However, due to the substantial increase in usage, the low safety performance of lithium-ion batteries has hindered their further development. Therefore, how to significantly improve the safety of lithium-ion batteries and further improve the energy density of lithium-ion batteries is an urgent problem to be solved in the academic community.

[0003] Studies have shown that the use of solid electrolytes can significantly improve the safety of lithium-ion batteries. In addition, the use of solid electrolytes with lithium metal negative electrodes can also effectively increase the energy density of batteries. However, solid-state batteries have poor fluidity and poor interface contact, which affects the cycle stability of the battery. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, in a first aspect, the present invention provides a method for preparing a multilayer composite solid electrolyte, comprising the following steps:

[0005] Step 1, mixing lithium salt A, polymer and solvent to obtain slurry A, coating slurry A on a substrate, and drying to obtain a negative electrode side solid electrolyte;

[0006] Step 2, mixing lithium salt B, polymer, MOF and solvent to obtain slurry B, coating slurry B on the solid electrolyte membrane on the negative electrode side, and drying to obtain an intermediate product;

[0007] Step 3, mixing lithium salt C, polymer and solvent to obtain slurry C, coating the slurry C on the intermediate product, and drying to obtain the multilayer composite solid electrolyte;

[0008] The lithium salt A includes any one of LiBOB (lithium bis(oxalatoborate) and LiDFOB (lithium difluorooxalatoborate) and LIFSI (lithium bis(fluorosulfonyl)imide); the lithium salt C includes any one of LiDFP (lithium difluorophosphate) and LiNO3 (lithium nitrate) and LIFSI.

[0009] Preferably, the mass ratio of LIFSI to other components in the lithium salt A is 1:0.01-0.05.

[0010] Preferably, the LIFSI concentration in slurry A is 0.3-0.7 mol / L.

[0011] Preferably, the lithium salt B is any one of LIFSI and LiTFSI (lithium bis(trifluoromethylsulfonyl)imide).

[0012] Preferably, the concentration of lithium salt B in slurry B is 0.1-0.3 mol / L; the mass ratio of polymer to MOF material in slurry B is 1:0.05-0.2.

[0013] Preferably, the mass ratio of LIFSI to other components in the lithium salt C is 1:0.01-0.05.

[0014] Preferably, the LIFSI concentration in slurry C is 0.3-0.7 mol / L.

[0015] Preferably, in steps 1 to 3, the polymers are any one or more of PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), and PVDF-CTFE (polyvinylidene fluoride-chlorotrifluoroethylene).

[0016] Preferably, the concentration of the polymer in slurry A, slurry B and slurry C is 80-130 g / L.

[0017] Preferably, in steps 1 to 3, the solvent is any one or two of DMF (N,N-dimethylformamide) and THF (tetrahydrofuran).

[0018] Preferably, the drying process in steps 1 to 3 is the same, which is to stand and dry at room temperature for 12 to 24 hours, and then dry in a 90 to 100° C. forced air oven for 1 to 2 hours.

[0019] In a second aspect, the present invention provides a multilayer composite solid electrolyte prepared by the above-mentioned preparation method; the multilayer composite solid electrolyte includes a negative electrode side solid electrolyte, an intermediate layer solid electrolyte, and a positive electrode side electrolyte, and the negative electrode side solid electrolyte, the intermediate layer solid electrolyte and the positive electrode side electrolyte have at least partial overlapping areas.

[0020] In a third aspect, the present invention provides a battery comprising the above-mentioned multi-layer composite solid electrolyte.

[0021] Compared with the prior art, one or more technical solutions provided by the present invention have at least the following beneficial effects:

[0022] (1) The multilayer composite solid electrolyte provided by the present invention adds different lithium salts as fillers on the negative electrode side and the positive electrode side under the premise that LiFSI remains unchanged, which can improve the battery's adaptability to high voltage stability and lithium stability. MOF materials are filled in the middle layer solid electrolyte to increase the internal ion conductivity; the multilayer composite design effectively improves the battery's cycle stability and voltage window.

[0023] (2) The preparation method provided by the present invention is simple, the production conditions are green and clean, and the efficient preparation of high-performance solid electrolytes for lithium-ion batteries can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the cycle performance of batteries assembled from composite solid electrolytes prepared in specific embodiments 1 to 3 and comparative examples 1 to 4 of the present invention;

[0025] Figure 2 This is a high-voltage window test diagram of a battery assembled from solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0026] The present invention provides the following specific technical solutions.

[0027] In view of the defects and shortcomings of the prior art, in a first aspect, the present invention provides a method for preparing a multilayer composite solid electrolyte, comprising the following steps:

[0028] Step 1, mixing lithium salt A, polymer and solvent to obtain slurry A, coating slurry A on a substrate, and drying to obtain a negative electrode side solid electrolyte;

[0029] Step 2, mixing lithium salt B, polymer, MOF and solvent to obtain slurry B, coating slurry B on the solid electrolyte membrane on the negative electrode side, and drying to obtain an intermediate product;

[0030] Step 3, mixing lithium salt C, polymer and solvent to obtain slurry C, coating the slurry C on the intermediate product, and drying to obtain the multilayer composite solid electrolyte;

[0031] The lithium salt A includes any one of LiBOB (lithium bis(oxalatoborate) and LiDFOB (lithium difluorooxalatoborate) and LIFSI (lithium bis(fluorosulfonyl)imide); the lithium salt C includes any one of LiDFP (lithium difluorophosphate) and LiNO3 (lithium nitrate) and LIFSI.

[0032] The inventor has found through research that the preparation of a fully solid electrolyte composed of three parts, namely the negative electrode side, the intermediate layer and the positive electrode side, can improve the interfacial stability between the electrolyte and the positive and negative electrodes, solve the problem of large intrinsic polarization of the solid electrolyte, and improve the cycle stability and voltage window of the battery. The lithium salts in the solid electrolyte on the negative electrode side and the solid electrolyte on the positive electrode side use different lithium salts as fillers based on the premise that LiFSI remains unchanged. Different lithium salts have different properties, such as the characteristics of tolerance to oxidation or reduction. The enrichment of different lithium salts on the positive and negative electrode sides causes different reactions at the interface between the positive and negative electrodes, which increases the stability of the interface film, and generates different CEI films between the positive electrode side and the positive electrode, and between the negative electrode side and the negative electrode, thereby solving the compatibility problem between the solid electrolyte and the positive and negative electrodes; adding MOF materials to the electrolyte increases the problem of low lithium ion mobility in the solid electrolyte.

[0033] The inventors further discovered that it is difficult to achieve both reduction and oxidation resistance using the same lithium salt in a layered solid electrolyte. A certain lithium salt is extremely stable on the positive electrode side but may not be stable on the negative electrode side. Therefore, the present invention adds different lithium salts as fillers to the positive and negative electrodes of the solid electrolyte on the negative electrode side and the solid electrolyte on the positive electrode side on the premise that LiFSI remains unchanged, which can improve the battery's adaptability to high voltage stability and lithium stability.

[0034] Preferably, the mass ratio of LIFSI to other components in the lithium salt A is 1:0.01-0.05.

[0035] Preferably, in slurry A, the concentration of LIFSI is 0.3-0.7 mol / L.

[0036] Preferably, the lithium salt B is any one of LIFSI and LiTFSI (lithium bis(trifluoromethylsulfonyl)imide).

[0037] Preferably, the concentration of lithium salt B in slurry B is 0.1-0.3 mol / L; the mass ratio of polymer to MOF material in slurry B is 1:0.05-0.2.

[0038] Preferably, the mass ratio of LIFSI to other components in the lithium salt C is 1:0.01-0.05;

[0039] Preferably, the LIFSI concentration in slurry C is 0.3-0.7 mol / L.

[0040] In the actual production process, the amounts of lithium salt, polymer and solvent in slurry A, slurry B and slurry C can be adjusted according to the actual situation, and the ratio proposed in the present invention is only a preferred range.

[0041] Preferably, in steps 1 to 3, the polymers are any one or more of PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), and PVDF-CTFE (polyvinylidene fluoride-chlorotrifluoroethylene).

[0042] Preferably, the concentration of the polymer in slurry A, slurry B and slurry C is 80-130 g / L.

[0043] Preferably, in steps 1 to 3, the solvent is any one or two of DMF (N,N-dimethylformamide) and THF (tetrahydrofuran).

[0044] Preferably, the drying process in steps 1 to 3 is the same, which is to stand and dry at room temperature for 12 to 24 hours, and then dry in a 90 to 100° C. forced air oven for 1 to 2 hours.

[0045] In a second aspect, the present invention provides a multilayer composite solid electrolyte prepared by the above-mentioned preparation method; the multilayer composite solid electrolyte includes a negative electrode side solid electrolyte, an intermediate layer solid electrolyte, and a positive electrode side electrolyte, and the negative electrode side solid electrolyte, the intermediate layer solid electrolyte and the positive electrode side electrolyte have at least partial overlapping areas.

[0046] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0047] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0048] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0049] Embodiment 1:

[0050] (1) Take 5.6gLiFSI, 0.05813gLiBOB, and 10.0gPVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 500μm thick scraper to scrape on a glass plate; let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain a negative electrode side solid electrolyte membrane after drying;

[0051] (2) Take 5.612g LiFSI, 10.0g PVDF-HFP, and 1g ZIF-8 and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 700μm thick scraper to scrape on the negative electrode solid electrolyte membrane prepared in step (1); let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain an intermediate product after drying;

[0052] (3) Take 5.612g LiFSI, 0.0969g LiDFP, and 10.0g PVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 900μm thick scraper to scrape on the intermediate product obtained in step (2); then stand and dry at room temperature for 16h, and then dry in a 90℃ forced air oven for 1.5h to obtain a composite solid electrolyte after drying.

[0053] Embodiment 2:

[0054] (1) Take 7.9gLiFSI, 0.237gLiDFOB, and 8.0gPVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 500μm thick scraper to scrape on a glass plate, let it stand and dry at room temperature for 12h, and then dry it in a 95℃ forced air oven for 1h to obtain a negative electrode side solid electrolyte membrane after drying;

[0055] (2) Take 0.187g LiFSI, 1.0g PVDF-HFP, and 0.8g ZIF-8 and dissolve them in 10mL DMF. After fully stirring and dissolving, use a 700μm thick scraper to scrape on the negative electrode solid electrolyte membrane prepared in step (1), let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain an intermediate product after drying;

[0056] (3) Take 0.8gLiFSI, 0.024gLiNO3, and 0.8gPVDF-HFP and dissolve them in 10mL DMF. After fully stirring and dissolving, use a 900μm thick scraper to scrape on the intermediate product obtained in step (2), let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h. After drying, a composite solid electrolyte is obtained.

[0057] Embodiment 3:

[0058] (1) 11.06 g LiFSI, 5.53 g LiBOB, and 1.3 g PVDF were dissolved in 10 mL DMF. After being fully stirred and dissolved, the mixture was coated on a glass plate using a 500 μm thick scraper. The mixture was allowed to stand and dry at room temperature for 16 h, and then dried in a 90 °C forced air oven for 1.5 h. After drying, a negative electrode solid electrolyte membrane was obtained.

[0059] (2) Take 0.187g LiFSI, 1.0g PVDF, and 1.3g ZIF-8 and dissolve them in 10mL DMF. After fully stirring and dissolving, use a 700μm thick scraper to scrape on the negative electrode solid electrolyte membrane prepared in step (1), let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain a composite solid electrolyte membrane after drying;

[0060] (3) Take 1.1gLiFSI, 0.055gLiDFP, and 1.3gPVDF and dissolve them in 10mL DMF. After fully stirring and dissolving, use a 900μm thick scraper to scrape on the composite solid electrolyte membrane prepared in (2), let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain a composite solid electrolyte after drying.

[0061] Comparative Example 1:

[0062] (1) Take 5.6gLiFSI, 0.05813gLiBOB, and 10.0gPVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 500μm thick scraper to scrape on a glass plate; let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain a negative electrode side solid electrolyte membrane after drying;

[0063] (2) Take 5.612g LiFSI, 10.0g PVDF-HFP, and 1g ZIF-8 and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 700μm thick scraper to scrape on the negative electrode solid electrolyte membrane prepared in step (1); let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain an intermediate product after drying;

[0064] (3) Take 5.612g LiFSI, 0.0969g LiBOB, and 10.0g PVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 900μm thick scraper to scrape on the intermediate product obtained in step (2); then stand and dry at room temperature for 16h, and then dry in a 90℃ forced air oven for 1.5h to obtain a composite solid electrolyte after drying.

[0065] Comparative Example 2:

[0066] (1) Take 5.6gLiFSI, 0.05813gLiDFP, and 10.0gPVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 500μm thick scraper to scrape on a glass plate; let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain a negative electrode side solid electrolyte membrane after drying;

[0067] (2) Take 5.612g LiFSI, 10.0g PVDF-HFP, and 1g ZIF-8 and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 700μm thick scraper to scrape on the negative electrode solid electrolyte membrane prepared in step (1); let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain an intermediate product after drying;

[0068] (3) Take 5.612g LiFSI, 0.0969g LiDFP, and 10.0g PVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 900μm thick scraper to scrape on the intermediate product obtained in step (2); then stand and dry at room temperature for 16h, and then dry in a 90℃ forced air oven for 1.5h to obtain a composite solid electrolyte after drying.

[0069] Comparative Example 3:

[0070] (1) Take 5.6gLiFSI, 0.05813gLiBOB, and 10.0gPVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 500μm thick scraper to scrape on a glass plate; let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain a negative electrode side solid electrolyte membrane after drying;

[0071] (2) 5.612 g of LiFSI and 10.0 g of PVDF-HFP were dissolved in 100 mL of DMF, and after being fully stirred and dissolved, the mixture was coated on the negative electrode solid electrolyte membrane prepared in step (1) using a scraper with a thickness of 700 μm; the mixture was allowed to stand and dry at room temperature for 16 h, and then dried in a 90° C. forced air oven for 1.5 h to obtain an intermediate product after drying;

[0072] (3) Take 1.87gLiFSI, 0.032373gLiDFP, and 10.0gPVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 900μm thick scraper to scrape on the intermediate product obtained in step (2); then stand and dry at room temperature for 16h, and then dry in a 90℃ forced air oven for 1.5h to obtain a composite solid electrolyte after drying.

[0073] Comparative Example 4:

[0074] (1) Take 5.6gLiFSI, 0.05813gLiBOB, and 10.0gPVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 500μm thick scraper to scrape on a glass plate; let it stand and dry at room temperature for 16h, and then dry it in a 90℃ forced air oven for 1.5h to obtain a negative electrode side solid electrolyte membrane after drying;

[0075] (2) Take 5.612g LiFSI, 0.0969g LiDFP, and 10.0g PVDF-HFP and dissolve them in 100mL DMF. After fully stirring and dissolving, use a 900μm thick scraper to scrape the negative electrode side solid electrolyte membrane prepared in step (1); then stand and dry at room temperature for 16h, and then dry in a 90℃ forced air oven for 1.5h to obtain a composite solid electrolyte after drying.

[0076] The composite solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were cut into discs with a diameter of 19 mm to serve as solid electrolytes, and the lithium sheets were cut into discs with a diameter of 16 mm to serve as lithium battery negative electrodes. Commercial six-series (622) ternary positive electrode materials were mixed with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The mixture was placed in a small beaker and stirred at a speed of 800 r / min for 2 hours to obtain a slurry. Use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for 4 hours. After punching out a circular positive electrode sheet with a diameter of 12 mm, dry it in a vacuum drying oven at 105°C for 4 hours, place it in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode sheet during the transfer process, and assemble it into CR2032 button batteries in the glove box.

[0077] After the battery was assembled and aged for 12 hours, the charge and discharge tests at different potentials were carried out. The samples were cycled 100 times at a voltage of 2.8-4.5V and a current density of 0.5C. Figure 1 Schematic diagram of the cycle performance of the battery assembled with the composite solid electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 to 3, Figure 1 It can be seen that the battery assembled by the composite solid electrolyte provided by the present invention has better cycle stability. By comparing Example 1 with Comparative Example 1 and Comparative Example 2 respectively, it can be shown that adding different lithium salts as fillers in the solid electrolyte membrane on the negative electrode side and the solid electrolyte membrane on the positive electrode side on the premise that LiFSI remains unchanged can improve the cycle stability of the battery; comparing Example 1 and Comparative Example 3, the addition of no MOF will also increase the battery polarization and affect the battery cycle stability; comparing Example 1 and Comparative Example 4, it is shown that the three-layer structure solid electrolyte provided by the present invention has better cycle performance.

[0078] The batteries assembled with the solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to cyclic voltammetry tests at a scan rate of 1.0 mV / s. The test data are shown in Tables 1 and Figure 2 , Figure 2 This is a high-voltage window test diagram of a battery assembled from solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 4.

[0079] Table 1 High voltage windows of batteries assembled from solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 4

[0080]

[0081] Combining Table 1 and Figure 2 By comparing Example 1 with Comparative Example 1 and Comparative Example 2, it can be proved that the composite solid electrolyte provided by the present invention has a more excellent voltage window, indicating that the film-forming effect of lithium salt on the positive and negative electrodes significantly affects the electrolyte stability under high voltage; by comparing Example 1 with Comparative Example 3, it is shown that adding MOF material to the middle layer solid electrolyte can increase the mechanical properties of the solid electrolyte, and stabilize the electrolyte to avoid side reactions; by comparing Example 1 with Comparative Example 4, it is shown that the solid electrolyte with a three-layer structure provided by the present invention has a more excellent high-voltage window and can be applied to a larger voltage range.

[0082] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a multilayer composite solid electrolyte, characterized in that: The steps include: Step 1, mixing lithium salt A, polymer and solvent to obtain slurry A, coating slurry A on a substrate, and drying to obtain a negative electrode side solid electrolyte; Step 2, mixing lithium salt B, polymer, MOF and solvent to obtain slurry B, coating slurry B on the solid electrolyte membrane on the negative electrode side, and drying to obtain an intermediate product; Step 3, mixing lithium salt C, polymer and solvent to obtain slurry C, coating the slurry C on the intermediate product, and drying to obtain the multilayer composite solid electrolyte; Lithium salt A includes any one of LiBOB and LiDFOB and LIFSI; lithium salt C includes any one of LiDFP and LiNO3 and LIFSI; The mass ratio of LIFSI to other components in lithium salt A is 1:0.01-0.05; The mass ratio of LIFSI to other components in lithium salt C is 1:0.01~0.

05.

2. The method for preparing a multilayer composite solid electrolyte according to claim 1, characterized in that: The LIFSI concentration in slurry A is 0.3~0.7mol / L.

3. The method for preparing the multilayer composite solid electrolyte according to claim 1, characterized in that: The LIFSI concentration in slurry C is 0.3~0.7mol / L.

4. The method for preparing the multilayer composite solid electrolyte according to claim 1, characterized in that: The lithium salt B is any one of LIFSI and LiTFSI; the concentration of the lithium salt B in the slurry B is 0.1-0.3 mol / L.

5. The method for preparing the multilayer composite solid electrolyte according to claim 1, characterized in that: In steps 1 to 3, the polymers are any one or more of PVDF, PVDF-HFP, and PVDF-CTFE.

6. The method for preparing a multilayer composite solid electrolyte according to claim 1, characterized in that: The concentrations of the polymers in slurry A, slurry B and slurry C are all 80-130 g / L; the mass ratio of the polymer to the MOF material in slurry B is 1:0.05-0.

2.

7. The method for preparing a multilayer composite solid electrolyte according to claim 1, characterized in that: In steps 1 to 3, the solvent is any one or both of DMF and THF.

8. The method for preparing a multilayer composite solid electrolyte according to claim 1, characterized in that: The drying process in steps 1 to 3 is the same, which is to stand and dry at room temperature for 12 to 24 hours, and then dry in a 90 to 100° C. forced air oven for 1 to 2 hours.

9. A multilayer composite solid electrolyte, characterized in that: Prepared by the preparation method of the multilayer composite solid electrolyte according to any one of claims 1 to 8; the multilayer composite solid electrolyte comprises a negative electrode side solid electrolyte, an intermediate layer solid electrolyte, and a positive electrode side electrolyte, and the negative electrode side solid electrolyte, the intermediate layer solid electrolyte and the positive electrode side electrolyte have at least partial overlap.

10. A battery, characterized in that: Comprising a multilayer composite solid electrolyte as described in claim 9.

Citation Information

Patent Citations

  • Solid electrolyte and preparation method thereof, and solid battery containing solid electrolyte

    CN110518277A

  • PEO-based composite solid electrolyte adaptive to high-voltage positive electrode and preparation method of PEO-based composite solid electrolyte

    CN116646589A

  • Preparation method and application of polymer composite solid electrolyte with multilayer heterostructure

    CN118970169A